The Relationship between Response Time, Service Quality, Price Fairness and Facilities on Patient Satisfaction in the Dental Clinic of Sitanala Tanggerang Hospital - Prizka Zulkarnain; Innocentius Bernarto (Dinasti International Journal of Education Management And Social Science, 2024)
This study aims to examine and analyze the relationship between response time, service quality, price fairness, and facilities on patient satisfaction at the dental polyclinic of RSUP Sitanala Tangerang. The convenience sampling technique was used to get 229 samples of outpatient dental polyclinic patients at RSUP Sitanala Tangerang were sampled. Data were collected through a Google Form questionnaire and analyzed using the PLS-SEM method with the embedded two-stage approach. The results of the study show that response time, service quality, price fairness, and facilities have a positive and significant effect on patient satisfaction at the dental polyclinic of RSUP Sitanala Tangerang. This study examines the relationship between response time, service quality, price fairness, and facilities on patient satisfaction in the dental clinic of RSUP Sitanala Tangerang, which has not been widely studied before in the specific context of dental clinics. The results of this study can be used as an evaluation to improve hospital services. Hospital management should review their pricing strategies, increase investment in infrastructure, ensure comfortable and clean facilities, ensure fast and efficient response times, and enhance service quality through continuous training to meet patient expectations. Future research should involve more clinics from various regions and consider additional variables that affect patient satisfaction.